Diverse seeds and planting materials supporting farm resilience, inclusive value chains and healthy diets in a sustainable food system - Quantitative evaluation of community seed bank initiative among indirect beneficiaries in Vihiga County, Kenya (November 2023) - Termote, Celine; Aluso, Lillian Olimba; Akingbemisilu, Tosin Harold (2024)
This project adopts a participatory research approach aimed at empowering communities to take collective action for the conservation and utilization of diverse seeds and crops, to ultimately enhance farm and dietary diversity, contributing to improved nutrition, livelihoods, and incomes. The study specifically evaluates the impact of the community seed bank initiative on indirect beneficiaries in Vihiga County. This is to understand the ripple effects of direct beneficiaries' engagement, examining how their actions have positively influenced the outcomes for indirect beneficiaries, i.e. those who have interacted with direct beneficiaries. This population of interest provides a unique opportunity to generate innovative insights into the linkages between community seed banks, improved access to diverse, high-quality seeds, on-farm biodiversity, the availability of nutritious biodiverse foods, and healthier diets among indirect beneficiaries.